The Political Economy Determinants of Domestic Tax Mobilization in Developing Countries - Hélène Ehrhart (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2009)
To what extent differences across developing countries in their domestic tax mobilization can be explained, in addition to the traditional determinants, by political economy factors and particularly by the political regime? Using a panel of 78 developing countries over the period 1990-2005, this paper provides econometric evidence that democracy matters for achieving higher domestic tax revenues which are much needed to finance public goods. It is especially the level of constraints on the executive which is of importance to counter the government's propensity to cave in for special interests and to be insufficiently welfare minded. We found that high levels of democracy are specifically needed in natural resource rich countries to make natural resource rents contribute to higher domestic tax revenues and no longer be an impediment to a sustained tax system.
Keywords: H11; H20; O11; 330; Revenue Performance; Democracy; Developing Countries